Optimization for photocatalytic color removal of turquoise blue dye C.I. 199 in immobilized AC - Gallo, Jurex (Asean Engineering Journal)
The aim of the study is to optimize the process parameters in photocatalytic color removal of Turquoise blue dye (TBD) using immobilized Titania-activated carbon (AC/TiO2) and UV-system. A preliminary study was performed which revealed that 5 percent is the best AC loading in AC/TiO2. The immobilized AC/TiO2 with 5 percent AC loading was characterized using BET, SEM, TEM and TGA techniques. The point of zero change (pHpzc) of the composite catalyst was also determined. Response surface methodology (RSM) based on Central composite design (CCD) was applied in optimization. The cumulative effect of operating parameters initial dye concentration, catalyst loading, initial solution pH, UV intensity and recirculating flow rate on the efficiency of immobilized AC/TiO2 for Turquoise blue dye removal were evaluated. A mathematical model was proposed and the analysis of variance (ANOVA) indicated that the derived model could be used to navigate the design space. The mathematical model is correlated to the experimental value with a correlation coefficient of 0.93. The optimum operating parameters were found to be 15 ppm initial dye concentration, initial dye solution pH of 3.0, 3 g/L catalyst loading, recirculating flow rate at 100 ml/s and UV intensity of 2.5 mW/cm2. The initial dye concentration has the highest influence in color removal while the recirculating flow rate is found as the least significant factor. These optimum conditions exhibited 90.0 percent and 86.4 percent color removal for Turquoise blue dye and textile wastewater with TBD stream respectively.